Multiple First Names in the Netherlands (1760–2014). (2nd January 2016) - Bloothooft, Gerrit; Onland, David
Abstract : Although in Europe the custom to choose more than one name for a child first arose in the early Renaissance in Italy, its popularity reached the Netherlands only in the eighteenth century. On the basis of a high-coverage sample of the birth and name information for 26 million individuals from 1760 until 2014, the preference for multiple first names in the Netherlands has been studied, both annually and geographically. With the exception of recent years, religion has played a dominant role in name choices, including the number of names. Protestants only started to adopt double names in the nineteenth century, while Catholics increasingly chose three names, many including Maria (but only during a period of 50 years in the mid-twentieth century for boys). A tax proposal in 1915 on the number of names not only demonstrates the effect of financial cost on naming, but also the consistency of parents' name choices concerning their children. Whereas during previous centuries the changes were gradual, preferences varied rapidly over the last 50 years.